2017
DOI: 10.1007/s11274-017-2223-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of riboflavin in decolourisation of Congo red and bioelectricity production using Shewanella oneidensis-MR1 under MFC and non-MFC conditions

Abstract: Abstract:9 Dissimilatory metal reducing bacteria can exchange electrons extracellularly and hold great 10 promise for their use in simultaneous wastewater treatment and electricity production. This study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The results shown in Table indicate that riboflavin was 18.26 mg mL ‐1 for E. coli with insert MtrA , this was followed by that produced by MtrC (12.9 mg mL ‐1 ), and the lowest production was by that containing MtrCAB insert and E. coli (6.3 and 4.2 mg/mL, respectively). These results confirm that riboflavin production is increased as compensation for the lack of MtrC gene, as reported in previous work . Results for CE% followed the order MtrC > MtrA > MtrCAB > WT.…”
Section: Resultssupporting
confidence: 91%
“…The results shown in Table indicate that riboflavin was 18.26 mg mL ‐1 for E. coli with insert MtrA , this was followed by that produced by MtrC (12.9 mg mL ‐1 ), and the lowest production was by that containing MtrCAB insert and E. coli (6.3 and 4.2 mg/mL, respectively). These results confirm that riboflavin production is increased as compensation for the lack of MtrC gene, as reported in previous work . Results for CE% followed the order MtrC > MtrA > MtrCAB > WT.…”
Section: Resultssupporting
confidence: 91%
“…The results show that azo reduction is at its best at low nitrate concentrations, whereas high nitrate concentrations affected the biodegradation, this result is in agreement with Cirik et al (2013) who reported an adverse effect on azo dye reduction at high nitrate concentrations. Competition between nitrate and another electron acceptor compound such as azo dyes have been reported (Gomaa et al 2017). The same competition was reported for a co-polluted media containing nitrate and perchlorate suggesting that nitrate has a lower energy barrier for proton and electron transfer (Lv et al 2020).…”
Section: Biophysical Changes Of Bacillus Sp In the Presence Of Different Nitrate Concentrationsmentioning
confidence: 99%
“…The anode and the cathode compartments were separated with a cationexchange membrane CMI-7000 (Membranes International USA). The anaerobic anode compartment containing 200 ml working volume was purged with nitrogen gas for 10 min through a 0.22 µm pore size diameter filter prior to inoculation; the media used were MSM prepared according to Gomaa et al (2017), which contained the following (g/L): NH 4 Cl 0.46, KCl 0.225, MgSO 4 .7H 2 O 0.117, NaH 2 PO 4 2.5, Na 2 HPO 4 4.11, (NH 4 ) 2 SO 4 0.225; a vitamin mixture and trace mineral solution were added (1%), and 500 mg/L casein hydrolyzate and 2.2 g/L sodium pyruvate were also added. Cathode chamber contained 200 ml working volume of 100 mM potassium ferricyanide in 50 mM sodium phosphate buffer (pH 7).…”
Section: Enrichment and Characterization Of Anodic Bacteriamentioning
confidence: 99%
“…The use of MFCs in the treatment of textile wastewater has been reported as an alternative approach to classical chemical and physical textile wastewater treatment due to its efficiency and low cost. The decolorization process can increase upon optimizing the operation conditions (Eslami et al, 2019), by adding redox mediators in the anodic chamber (Gomaa, Fapetu, Kyazze, & Keshavarz, 2017) or through incorporating a novel MFC design. During an MFC process, electrons are transferred from the microorganism to the anode, and then they flow through a circuit to the cathode.…”
Section: Introductionmentioning
confidence: 99%